(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
On the 1st of July 2021, the second phase of 548/2014 EU Regulation, which implements the 2009/125/EC Directive and imposes the maximum level of losses for transformers, entered into force. Some manufacturers have responded to the challenge of reducing the losses by manufacturing power transformers with an elongated core cross-section. In this context, the paper proposes an algorithm to generalize the steps (stacks of laminations) sizing procedure for the core cross-section of power transformers, an algorithm that allows the transition from a circular to an oblong core cross-section. Thus, the dimensions of the laminations stacks which is making up the core cross-section could be estimated for any predetermined value of cross-section diameter. An example of using the proposed algorithm and the impact analysis of the oblong cross-section is applied for an oil cooling power three-phase transformer with a 250kVA rated power. For the oblong cross-section design solution, decreases of the transformer core dimensions and the no-load losses were obtained.